2021
DOI: 10.1021/acsnano.0c06701
|View full text |Cite
|
Sign up to set email alerts
|

Structural Defects Modulate Electronic and Nanomechanical Properties of 2D Materials

Abstract: This document is made available in accordance with publisher policies and may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the URL above for details on accessing the published version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 57 publications
1
59
0
Order By: Relevance
“…The ALD-grown SnS thin film has an orthorhombic structure, as indicated by Raman peak at 159 cm –1 , and is expected to have in-plane 2D ferroelectricity (Figure b ) , but the out-of-plane piezoelectric response is not generally expected. Nevertheless, the out-of-plane piezoelectric coefficient, d 33 , can still be observed due to structural defects, interface roughness, atomic vacancies, and an incomplete phase transition. , To determine the optimal thickness of each layer, we have prepared the PENG with different layer thicknesses of 2.5, 5, 7.5, and 10 nm for both SnS 2 and SnS. With the prepared thin films, the piezoelectric output performance of each device was examined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ALD-grown SnS thin film has an orthorhombic structure, as indicated by Raman peak at 159 cm –1 , and is expected to have in-plane 2D ferroelectricity (Figure b ) , but the out-of-plane piezoelectric response is not generally expected. Nevertheless, the out-of-plane piezoelectric coefficient, d 33 , can still be observed due to structural defects, interface roughness, atomic vacancies, and an incomplete phase transition. , To determine the optimal thickness of each layer, we have prepared the PENG with different layer thicknesses of 2.5, 5, 7.5, and 10 nm for both SnS 2 and SnS. With the prepared thin films, the piezoelectric output performance of each device was examined.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the out-of-plane piezoelectric coefficient, d 33 , can still be observed due to structural defects, interface roughness, atomic vacancies, and an incomplete phase transition. 35,36 To determine the optimal thickness of each layer, we have prepared the PENG with different layer thicknesses of 2.5, 5, 7.5, and 10 nm for both SnS 2 and SnS. With the prepared thin films, the piezoelectric output performance of each device was examined.…”
Section: Resultsmentioning
confidence: 99%
“…There is also enduring interest in the technological applications of two-dimensional (2D) materials, including graphene, for display devices [28], flexible sensors [29][30][31], photo detectors [32][33][34][35][36], vertical field-effect transistors [37,38], and atom chips [27]. New properties and methods of cooling or patterning 2D materials have been studied [39][40][41][42][43][44][45][46][47]. As current-carrying wires in atom chips, graphene has desirable electronic properties: it has a very low density of electronic states, high carrier mobility and a linear band structure with zero band gap in the vicinity of the Dirac points [48], which leads to Johnson noise and CP attraction far below those typically found for metallic conductors on bulk substrates [19,20,27,49].…”
Section: Introductionmentioning
confidence: 99%
“…[30] However, the substrate on which graphene is deposited plays a pivotal role in modulating the mechanical, physical, and electronic properties. [31,32] In particular, strain induced by interaction with a substrate is one of the most intriguing parameters to adapt and tune graphene characteristics. [33,34] The role of substrate shape and its interfacial adhesion with graphene was theoretically studied by Wagner et al, [35] who observed "snap-through" event of graphene under different textured confinements.…”
Section: Introductionmentioning
confidence: 99%